The Jews of Medieval Islam: Community, Society and Identity. Proceedings of an International Conference held by the Institute of Jewish Studies, University College London 1992 - Frank, Daniel (Études sur le judaïsme médiéval, 1995)
This volume contains fifteen articles on the communal, social, and intellectual life of medieval Jewry in Islamic lands. The book is divided into three parts. Part I, 'Communities and Their Leaders' is devoted to the old Babylonian center in the East and the Andalusian community in the West. Part II, 'Self-Perceptions and Attitudes Towards Others' investigates the ways in which medieval Jews living under Islam viewed their gentile neighbours and expressed their own identity. Part III, 'Religious Philosophy, Mysticism, and Spirituality in Islam and Judaism' explores the impact of Islamic thought on the Jewish intellectual tradition. The collection depicts a civilization at once unified and diverse, revealing both consistent patterns of leadership and scholarship as well as distinctively local identities and collective memories